The biomolecular spectrum drives microbial biology and functions in agri-food-environments - Sharma M.; Singh D.P.; Rangappa K.S.; Stadler M.; Mishra P.K.; Silva R.N.; Prasad R.; Gupta V.K. (My University, 2025)
Microbial biomolecules have huge commercial and industrial potential. In nature, biological interactions are mostly associated with biochemical and biological diversity, especially with the discovery of associated biomolecules from microbes. Within cellular or subcellular systems, biomolecules signify the actual statuses of the microorganisms. Understanding the biological prospecting of the diverse microbial community and their complexities and communications with the environment forms a vital basis for active, innovative biotechnological breakthroughs. Biochemical diversity rather than the specific chemicals that has the utmost biological importance. The identification and quantification of the comprehensive biochemical diversity of the microbial molecules, which generally consequences in a diversity of biological functions, has significant biotechnological potential. Beneficial microbes and their biomolecules of interest can assist as potential constituents for the wide-range of natural product-based preparations and formulations currently being developed on an industrial scale. The understanding of the production methods and functions of these biomolecules will contribute to valorisation of agriculture, food bioprocessing and biopharma, and prevent human diseases related to the environment. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.